2019
DOI: 10.1002/joc.5997
|View full text |Cite
|
Sign up to set email alerts
|

Potential contributions of climate change and urbanization to precipitation trends across China at national, regional and local scales

Abstract: Climate change and urbanization collectively influence precipitation changes. However, their separate potential contributions to precipitation changes are not well understood due to their complex interactions. Hence, a “trajectory”‐based method was used to separate their potential contributions across national, regional and local scales in China. Precipitation changes in non‐urban regions can be regarded as representing the influence of climate change and can serve as a reference for isolating precipitation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 59 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…To reduce the impact of any regional confounding factors, we pair rural and urban stations by selecting urban stations that are located within a 100-km buffer of rural stations (Gu et al, 2019b;Luo & Lau, 2018). The above analyses are repeated based on the paired rural-urban stations (Figures S12-S14 and Text S3 in Supporting Information S1).…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the impact of any regional confounding factors, we pair rural and urban stations by selecting urban stations that are located within a 100-km buffer of rural stations (Gu et al, 2019b;Luo & Lau, 2018). The above analyses are repeated based on the paired rural-urban stations (Figures S12-S14 and Text S3 in Supporting Information S1).…”
Section: Resultsmentioning
confidence: 99%
“…For Dahuangjiangkou station, it was found that the nonstationary flood hazard calculated using time covariates was always larger than the stationary flood hazard, since the future exceedance probabilities p t in Equation (4) were getting monotonically larger with time covariates, while the cases were complicated for the nonstationary flood hazard calculated using pop and rain covariates because p t grew in fluctuation with pop and rain covariates ( Figure 11). In addition, the nonstationary flood hazard calculated using pop and rain covariates was larger than that calculated using time covariate for m ∈ [2,30]. For Huaxian station, the nonstationary flood hazard estimated by time or physical covariates were all smaller than stationary flood hazard because the AMFS were decreasing and the exceedance probabilities p t in Equation (4) were getting smaller (Figure 12), indicating that the flood hazard in the Huaxian basin will decrease in future periods.…”
Section: Flood Hazard Analysis For Prb and Wrbmentioning
confidence: 96%
“…The fundamental assumption of the conventional flood frequency analysis is that the annual maximum flood series (AMFS) is independent and identically distributed (iid), also known as the stationary assumption. However, this assumption has been challenged by climate change and human activities [1][2][3][4][5][6][7][8][9][10][11][12]. Thus, the conventional stationary flood frequency analysis should be adapted to nonstationary conditions in changing environments.…”
Section: Introductionmentioning
confidence: 99%
“…We used a 1 • × 1 • grid spacing as the basic analysis unit, as in Burke and Stott (2017) and Gu et al (2019). We considered the grid with all its surrounding grids (out of eight possible) as a 3 • × 3 • window (figure S3).…”
Section: Detection Of the Long-term Trend Of Extreme Precipitationmentioning
confidence: 99%